2010
DOI: 10.1017/s0022215110002422
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and recurrent conductive deafness following stapedotomy

Abstract: The best chance of obtaining a successful outcome in stapedotomy is to achieve this for the first procedure. However, revision surgery does increase the medium to long term success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…Comparable to the findings described in the literature, 2 , 12 stapedotomy was associated with better results, in that this technique was performed in most of the patients requiring only a single surgical intervention. The hearing results presented in this study are similar to those of previous studies 3 , 6 , 9 demonstrating reduced hearing outcomes following revision surgery.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Comparable to the findings described in the literature, 2 , 12 stapedotomy was associated with better results, in that this technique was performed in most of the patients requiring only a single surgical intervention. The hearing results presented in this study are similar to those of previous studies 3 , 6 , 9 demonstrating reduced hearing outcomes following revision surgery.…”
Section: Discussionsupporting
confidence: 50%
“…Various other causes of prosthesis failure do exist and have been described in the literature. 2 , 3 , 5 , 6 Factors such as incus erosion or prosthesis malfunction itself, which can contribute to primary procedure failure, have been excluded from our study and thus are thought not to be contributing factors in the results demonstrated here. The retrospective nature of this study, however, does include certain limitations.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations